2007
DOI: 10.1093/gerona/62.12.1435
|View full text |Cite
|
Sign up to set email alerts
|

Does Physician Communication Influence Older Patients' Diabetes Self-Management and Glycemic Control? Results From the Health and Retirement Study (HRS)

Abstract: Among these older adults, both their diabetes providers' provision of information and efforts to actively involve them in treatment decision-making were associated with better overall diabetes self-management. Involving older patients in setting chronic disease goals and decision-making, however, appears to be especially important for self-care areas that demand more behaviorally complex lifestyle adjustments such as exercise, diet, and blood glucose monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 43 publications
4
111
3
2
Order By: Relevance
“…The implication of this finding is that diabetes-related distress is significantly reduced when the doctor-patient relationship provides the patient with a greater perceived capacity to self-manage their condition. It has been suggested that such communication techniques as i) encouraging patients to repeat back in their own words the information provided by a practitioner, ii) tailoring information provision to the patients' own health concerns and previous experiences, and iii) explaining the impact of recommended self-care behaviours on future health outcomes, can all positively impact upon diabetes self-care (Heisler et al, 2007). Further, Ha and Longnecker (2010) Our findings support previous studies which suggest that the doctor-patient relationship is associated with psychological wellbeing in diabetes patients (Beverly et al, 2012;Rose et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The implication of this finding is that diabetes-related distress is significantly reduced when the doctor-patient relationship provides the patient with a greater perceived capacity to self-manage their condition. It has been suggested that such communication techniques as i) encouraging patients to repeat back in their own words the information provided by a practitioner, ii) tailoring information provision to the patients' own health concerns and previous experiences, and iii) explaining the impact of recommended self-care behaviours on future health outcomes, can all positively impact upon diabetes self-care (Heisler et al, 2007). Further, Ha and Longnecker (2010) Our findings support previous studies which suggest that the doctor-patient relationship is associated with psychological wellbeing in diabetes patients (Beverly et al, 2012;Rose et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes educators work within a culture of medicine that has its own medical jargon and focus on pathophysiology that is different than the lay culture of patients and families. (Anderson et al, 2007;Swedlund et al, 2012), self-care (Heisler, Cole, Weir, Kerr, & Hayward, 2007), adherence to treatment (Zolnierek & DiMatteo, 2009), and health outcomes (Aikens, et al, 2005 (Castro, Wilson, Wang, & Schillinger, 2007;Katz, Jacobson, Veledar, & Kripalani, 2007;Sudore et al, 2009) …”
Section: Essential Assumptions Of the Modelmentioning
confidence: 99%
“…Heisler, Cole, Weir, Kerr and Hayward [21] using two validated scales to access medical advice found that when providers communicated information and allowed * Models 1 and 2 are adjusting for diabetes medications, perceived stress score, age, gender, body mass index, years with diabetes, self-rated health, health insurance, depression, marital status, ducation, smoking, and physical activity. In addition, Model 1 is adjusted for A1C.…”
Section: Discussionmentioning
confidence: 99%